Constructing the Military Hero - Cavender, Gray (2013)
Today we see an increase in the usage of the term hero. Especially in the media, the term is applied not only to those who do specific heroic deeds but to entire professions, e.g., the military. In this paper, we analyze the media's social construction of military heroes with respect to four individuals, two fictional characters and two real people. We argue that four themes are essential to the construction of the military hero whether for fictional or real people: a biography; strength of purpose; gender; and the reinforcement of national values. Once constructed in the media, the hero often contributes to political ends by reinforcing national values. More specifically, in their construction military heroes reflect and reproduce ideologies that legitimate the state and its military aggressiveness